Charge-transfer induced multifunctional BCP:Ag complexes for semi-transparent perovskite solar cells with a record fill factor of 80.1%. Issue 20 (6th April 2021) - Ying, Zhiqin; Yang, Xi; Zheng, Jingming; Zhu, Yudong; Xiu, Jingwei; Chen, Wei; Shou, Chunhui; Sheng, Jiang; Zeng, Yuheng; Yan, Baojie; Pan, Hui; Ye, Jichun; et al.
Abstract : A charge-transfer induced BCP:Ag complex is employed as a multifunctional buffer layer for efficient inverted semi-transparent perovskite solar cells. Abstract : For semi-transparent perovskite solar cells (PSCs), the bombardment during the deposition of a transparent conductive oxide would inevitably damage the underlying soft materials, thereby inducing a high density of defects and creating an unfavorable band mismatch at the interface. Although interfacial buffer layers can be adopted to alleviate this bombardment damage, the device performance is still limited by the inferior fill factor (FF) due to the increased series resistance and the decreased carrier collection. In this work, a charge transfer induced 2, 9-dimethyl-4, 7-diphenyl-1, 10-phenanthroline (BCP):Ag complex is employed to mediate the electrical contact between a C60 electron-transport layer and sputtered indium-zinc oxide (IZO) top electrode. We demonstrate that the multifunctional BCP:Ag complex can (1) reduce the electron extraction barrier by pulling up the Fermi level of BCP, (2) create beneficial gap states for electron transport, (3) serve as a hole blocking layer to suppress charge recombination, and (4) protect the C60 underlayer from the sputtering damage. As a result, the optimized electrical contact at the C60 /BCP:Ag/IZO interface significantly recovered the FF of the inverted semi-transparent perovskite solar cell from 71.8% to 80.1%, yielding a device efficiency of 18.19%. By using a 23.19% efficient silicon solar cell, we also demonstrate a four-terminal tandem configuration with a total efficiency of 27.59%.